Video completion using gray level co-occurrence matrix and object update - Zarif, Samih; Faie, Ibrahima; Rohaya, Dayang (International arab journal of information technology, 2016)
Reconstructing and repairing damaged parts after object removal of digital video is an important trend in artwork restoration. Video completion is an active subject in video processing, which deals with the recovery of the original data. Most previous video completion approaches consume more time in extensive search to find the best patch to restore the damaged frames. In addition to that, visual artifacts appear when the damaged area is large. This paper presents a video completion method without the extensive search process. The proposed framework consists of a segmentation stage based on low resolution version and background subtraction, a tracking stage based on Gray Level Co-occurrence Matrix (GLCM), and a completion stage based on object prior position and object update. The proposed method reduces the completion time to a few seconds and maintains the spatial and temporal consistency. It works well when the background has clutter or fake motion, and it can handle changes in object size and in posture.